Results of long-term follow-up of patients with chronic gastritis after H. pylori eradication - T. L. Lapina; A. S. Tertychny; E. R. Nasretdinova; I. M. Kartavenko; A. V. Paraskevova; Ye. Yu. Yur’yeva; O. A. Storonova; A. S. Trukhmanov; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2015)
The aim of publication. To analyze approach for long-term management of patients with chronic gastritis after H. pylori eradication for stomach cancer prevention by the example of clinical cases.Key points. The management approach of patients with chronic gastritis after eradication of H. pylori is presented by the example of patients with various risk of development of stomach cancer. In one and half year after successful eradication therapy in 57 year-old female patient mild atrophy and intestinal metaplasia of antrum without atrophy and intestinal metaplasia of corpus of the stomach was confirmed. At absence of other risk factors for cancer development further endoscopic follow-up is not required. Monitoring of 62 year-old male patient after successful eradication for 5 years has shown stable morphological pattern without progression of premalignant lesions. Taking into account both severe atrophy and intestinal metaplasia of antral region and mild atrophy of body of the stomach, as well as positive family history, esophagogastroscopy with biopsy is recommended once per year to this patient.Conclusion. Prognosis and management approach of patients after eradication of H. pylori infection are determined by chronic gastritis in relation to severity of atrophy and intestinal metaplasia of antral region and corpus of the stomach, along with other risk factors for cancer development e.g. positive family history.